1979
DOI: 10.1002/ana.410060111
|View full text |Cite
|
Sign up to set email alerts
|

Periodic lateralized epileptiform discharges in infants and children

Abstract: Clinical and electroencephalographic data on 7 infants and children with periodic lateralized epileptiform discharges (PLEDS) in their electroencephalograms were reviewed. The waveform, periodicity, and transitory nature of these discharges were similar to those reported in adults. In children, as in adults, PLEDs reflect severe underlying brain dysfunction which is often associated with metabolic and structural abnormalities. In adults, PLEDs are usually associated with altered states of consciousness and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 10 publications
3
18
0
Order By: Relevance
“…They are most often associated with acute structural lesions, although they may also occur in the setting of metabolic derangements (1 3, [17][18][19]. We found that PEDs are also a marker of poor prognosis in SE, confirming the reports of Treiman (20) and Jaitly et al (21).…”
Section: Discussionsupporting
confidence: 88%
“…They are most often associated with acute structural lesions, although they may also occur in the setting of metabolic derangements (1 3, [17][18][19]. We found that PEDs are also a marker of poor prognosis in SE, confirming the reports of Treiman (20) and Jaitly et al (21).…”
Section: Discussionsupporting
confidence: 88%
“…83 The morphologic characteristics are similar to those of adults. 83 The morphologic characteristics are similar to those of adults.…”
Section: Periodic Lateralized Epileptiform Dischargesmentioning
confidence: 59%
“…83,86,87 The latter would be of particular concern if PLEDs developed during the convalescent phase of a child with a penetrating head wound. They have been reported with acute infarction due to sickle cell disease, metabolic imbalance, perinatal brain injury, cerebral cysticercosis, encephalitis, tumor, and brain abscess.…”
Section: Periodic Lateralized Epileptiform Dischargesmentioning
confidence: 99%
“…PLEDS, although a well known marker of stroke in adults, has only been infrequently reported in neonates with stroke [6,8]. PLEDS lacks specificity as it may be seen in neonatal herpes, structural and metabolic abnormalities [6,7].…”
Section: Discussionmentioning
confidence: 99%